Age, period and cohort effects on migration of the baby boomers in Australia - Nikola Sander; Martin Bell (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2012)
The differential migration behaviour of the baby boom generation is commonly explained by reference to cohort size effects. This paper focuses on inter-cohort differences in the intensity and pattern of internal migration in Australia, while paying particular attention to the Australian baby boomer generation as it has moved through the life-course. A series of generalised linear models are fitted to migration transition for age-period-cohort spaces to disentangle the effects of age, period and birth cohort on migration. The results demonstrate that the relative contribution of age to change in migration intensity is largest in relative terms, followed by cohort, while the effects of period were much more subtle. In comparison to earlier work on cohort effects in the United States that showed a negative effect of large cohort size on migration, cohort effects on migration are not restricted to the baby boom but show a continuous upwards trend across cohorts. We find that this divergence from the US-based evidence regarding cohort effects is largely due to the different timing and magnitude of the Australian baby boom compared to the US. The baby boom in Australia was delayed and much smaller in terms of absolute and relative cohort size than in the US. Results highlight the importance of factors other than cohort size, such as differences in attitudes to mobility and housing market dynamics, in shaping migration behaviour of the Australian baby boomers.
Keywords: 300; Internal migration; cohort analysis; baby boom; Australia; Binnenwanderung; Altersgruppe; Australien